KERAWANAN PANGAN WILAYAH DAN KETAHANAN PANGAN RUMAH TANGGA PETANI TEMBAKAU DAN JAGUNG - TINJUNG MARY PRIHTANTI; ENDRI EKA WARTA; ARIES KRISTYANTO (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2010)
Farmer, play multiple roles, as a producer and a consumer, majority live below prosperity, the biggest chances to be threatment by food security.